Answer:
x = 8
Explanation:
Solve for x:
-8 = (-3 x)/4 - 2
Put each term in (-3 x)/4 - 2 over the common denominator 4: (-3 x)/4 - 2 = (-8)/4 - (3 x)/4:
-8 = (-8)/4 - (3 x)/4
(-8)/4 - (3 x)/4 = (-3 x - 8)/4:
-8 = (-3 x - 8)/4
-8 = (-3 x - 8)/4 is equivalent to (-3 x - 8)/4 = -8:
(-3 x - 8)/4 = -8
Multiply both sides of (-3 x - 8)/4 = -8 by 4:
(4 (-3 x - 8))/4 = -8×4
(4 (-3 x - 8))/4 = 4/4×(-3 x - 8) = -3 x - 8:
-3 x - 8 = -8×4
4 (-8) = -32:
-3 x - 8 = -32
Add 8 to both sides:
(8 - 8) - 3 x = 8 - 32
8 - 8 = 0:
-3 x = 8 - 32
8 - 32 = -24:
-3 x = -24
Divide both sides of -3 x = -24 by -3:
(-3 x)/(-3) = (-24)/(-3)
(-3)/(-3) = 1:
x = (-24)/(-3)
The gcd of -24 and -3 is -3, so (-24)/(-3) = (-3×8)/(-3×1) = (-3)/(-3)×8 = 8:
Answer: x = 8